2013
DOI: 10.1186/2051-5960-1-73
|View full text |Cite
|
Sign up to set email alerts
|

In vivo modification of Abeta plaque toxicity as a novel neuroprotective lithium-mediated therapy for Alzheimer’s disease pathology

Abstract: BackgroundAlzheimer’s disease (AD) is characterized by the abnormal accumulation of extracellular beta-amyloid (Abeta) plaques, intracellular hyperphosphorylated tau, progressive synaptic alterations, axonal dystrophies, neuronal loss and the deterioration of cognitive capabilities of patients. However, no effective disease-modifying treatment has been yet developed. In this work we have evaluated whether chronic lithium treatment could ameliorate the neuropathology evolution of our well characterized PS1M146L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 53 publications
2
37
0
Order By: Relevance
“…As expected (Jimenez et al, 2008; Serrano‐Pozo, Muzikansky, et al, 2013; Serrano‐Pozo, Betensky, Frosch, & Hyman, 2016; Trujillo‐Estrada et al, 2013), the hippocampus of both the transgenic APP/PS1 model and Alzheimer's patients (Braak V–VI) displays significant astrogliosis (measured by GFAP expression and by the area covered by the reactive astrocytes; see also Jimenez et al, 2008), which progresses in parallel to the extracellular amyloid pathology. The increase in astrocytic reactivity involves both morphological (enlarged cell body and processes) and molecular changes (Osborn et al, 2016).…”
Section: Discussionsupporting
confidence: 75%
“…As expected (Jimenez et al, 2008; Serrano‐Pozo, Muzikansky, et al, 2013; Serrano‐Pozo, Betensky, Frosch, & Hyman, 2016; Trujillo‐Estrada et al, 2013), the hippocampus of both the transgenic APP/PS1 model and Alzheimer's patients (Braak V–VI) displays significant astrogliosis (measured by GFAP expression and by the area covered by the reactive astrocytes; see also Jimenez et al, 2008), which progresses in parallel to the extracellular amyloid pathology. The increase in astrocytic reactivity involves both morphological (enlarged cell body and processes) and molecular changes (Osborn et al, 2016).…”
Section: Discussionsupporting
confidence: 75%
“…Our study confirms previous studies showing a beneficial effect of lithium in animal models of AD and AD patients, while also highlighting the potential benefit of LISPRO. Although a few studies reported no effect of lithium chloride on Aβ levels (Caccamo, Oddo, Tran, & LaFerla, ; Feyt et al, ) or even neurodegeneration induced by tau suppression (Lei et al, ), the overriding evidence indicates that lithium treatment effectively reduces extracellular β‐amyloid (Habib et al, ; Trujillo‐Estrada et al, ) and tau hyperphosphorylation in cell culture and animal models of AD (Nery et al, ). Likewise, intracerebroventricular injection of Aβ in zebrafish embryo impairs cognition which was successfully reversed by lithium administration (Nery et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the characterization of plaques on the basis of their capacity to induce axonal and neuronal damage is crucial to validate animal models for research and drug testing. In this sense, our A␤PP/PS1 model is of great interest since these mice develop human-like neuritic plaques whose toxicity can be modulated in vivo, as we have recently shown, by lithium administration resulting in a marked reduc-tion of neuronal and axonal damage and cognitive improvement [66].…”
Section: Discussionmentioning
confidence: 99%